Analisis UX Pada Aplikasi SISMIOP Bapenda Kab. Pemalang Menggunakan Metode User Experience Questionnaire - Rita Aishwarya Rao; Resad Setyadi (STMIK Budi Darma, 2023)
At this time BAPENDA has been following globalization developments in the field of information technology which is useful for supporting the operational performance of financial management in a fast, accurate, precise and quality manner. At BAPENDA there is an information technology application, namely SISMIOP or an extension of the Information System and Management of Tax Objects. This study aims to find out how the perceptions of BAPENDA staff in Kab. Pemalang regarding the SISMIOP application or information system and management of tax objects, this study will explore system users through questionnaires given to district Bapenda office staff. Pemalang, in order to improve the service quality system. This analysis will facilitate the delivery of information to those who use it and those who need it. This study uses the UEQ method or the abbreviation of User Experience Questionnaire, because UEQ is quite efficient and effective for measuring User Experience. UEQ has 26 questions with a linear scale of 1 to 7. UEQ measures 6 user experience factors, namely attractiveness, perspicuity, efficiency, dependability, stimulation, and novelty. . The results of the research on measurement for each aspect obtained attractiveness values ??of 1,767, perspicuity of 1,800, efficiency of 1,600, dependability of 2,050, stimulation of 1,800, novelty of 1,550. On all scales get a positive impression. The benchmark results show that the dependability and stimulation aspects are included in the excellent criteria (very very), while other aspects are included in the good criteria